Perception of pre-hospital care professionals in urgency and emergency care (crisis) in psychiatry (Research, Society and Development, 2021)
Objective: To verify the evidence in the national and international literature on the perceptions of professionals in pre-hospital care, in relation to urgent and emergency care (crisis) in psychiatry. Method: Integrative review of articles published in English, Portuguese and Spanish. For the survey, electronic databases, BDENF, Lilacs and MEDLINE were used, using the descriptors in a combined way “Pre-hospital care” and “psychiatry”. The research was carried out through the Brazilian VHL Network / Virtual Health Library in September 2020, with seven articles being carefully selected. Result: In most of the studies analyzed, the results indicate that professionals working in the Mobile Emergency Care Service (SAMU) have, fear, fear and lack of preparation in care in the face of a psychic crisis, making care pathological and stigmatizing. Conclusion: the professionals of the Mobile Emergency Care Service (SAMU) are still tied to hospital-centric, biomedical care with an asylum model, with fear predominating and a gap in technical and scientific knowledge. Despite the changes acquired from the psychiatric reform, care remains based on the disease and the stigma it suggests.